Measuring Economic Fairness In Early Settlement Of Griya Hasanah Financing: Systematic Literature Review And KPIS Index Proposal - Muhammad Havy Martdadi; Mochammad Andre Agustianto (Universitas Islam Darul 'ulum Lamongan, 2026)
This study explores the concept of economic justice in the practice of early settlement within Islamic financing, with a particular emphasis on the Griya Hasanah housing scheme. The research employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol to ensure methodological transparency. Literature searches were conducted across Scopus, Web of Science, Sinta, and Google Scholar databases, covering the period 2015–2025, resulting in 42 relevant studies. The review reveals five central dimensions of justice in early settlement practices: margin fairness, contractual compliance, procedural transparency, risk distribution, and alignment with the objectives of maqasid al-shari‘ah. Findings indicate a notable gap between normative regulations, such as DSN-MUI Fatwa No. 153/2022, which emphasizes the importance of granting rebates and the diverse practices implemented by Islamic banks, particularly in calculating rebate proportions and ensuring contract clarity. As a scholarly contribution, this research proposes the development of a Key Performance Indicators of Settlement (KPIS) framework as a structured tool for measuring justice. The KPIS incorporates five dimensions with operational indicators, including margin ratios, disclosure of information, compensation policies, risk protection, and maqasid compliance. By applying this framework, Islamic financial institutions can evaluate and enhance early settlement practices more objectively and fairly, thereby improving accountability and strengthening public confidence in the Islamic financial system.